OPTIMALISASI STRATEGI PEMASARAN PARFUM: STUDI EMPIRIS TENTANG NIAT BELI YANG DIMEDIASI OLEH NILAI YANG DIRASAKAN - Vanezza Brenda Aurellia; Oen Eric Harianto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The perfume industry has experienced rapid development along with the increasing awareness of society regarding appearance, leading to more competitive market conditions. This situation demands that companies understand the factors influencing consumer decisions, specifically related to Packaging, Promotion, Brand Awareness, and Pricing Strategy in creating Perceived Value. The challenges faced in the perfume industry include low sales turnover due to high competition among competitors. This study aims to analyze the direct influence of Packaging, Promotion, Brand Awareness, and Pricing Strategy on Purchase Intention and the direct influence of these four variables on Perceived Value; the influence of Perceived Value on Purchase Intention; and the role of Perceived Value as a mediator. This study uses a quantitative method with purposive sampling techniques, distributing questionnaires with a total of 231 respondents. Data analysis will be conducted using Structural Equation Modeling (SEM) based on path analysis. The results of this research show that the marketing variables of Packaging, Promotion, and Pricing Strategy have a significant influence on Perceived Value and Purchase Intention, while Brand Awareness does not provide a significant impact. Perceived Value has been proven to be a mediator in enhancing the influence of the Promotion variable on Purchase Intention. These findings contribute theoretically to the development of literature on beauty product marketing and provide practical recommendations for players in the perfume industry.